Akciğer kanseri nedeniyle sitostatik tedavi gören bir olguda gelişen S aureus'a bağlı yumuşak doku infeksiyonu ve sepsis - (:unkn) unknown (My University, 2005)
0

We report a case with subcutaneous abscess and sepsis due to Staphylococcus aureus. A 65-year-old man with a history of cytostatic therapy due to small cell lung carcinoma presented to us with sign and symptoms referable to the arms, including pain, tenderness, induration and increased warmth in the arm. Methicillin susceptible S. aureus was isolated from the cultures. Debridement and surgical drainage of the abscess were done. Patient received adequate antibiotic treatment. Her systemic symptoms resolved in 3 days. At the 10thday of the treatment, patient had fever again. Although vancomisin therapy started, patient has died at the 11th day of the treatment.
Subcutaneous abscess and sepsis due to S aureus after cytostatic therapy due to small cell lung carcinoma
Keywords: Genel ve Dahili Tıp